Microbiome in Cladonia squamosa Is Vertically Stratified According to Microclimatic Conditions - Noh, Hyun-Ju; Lee, Yung Mi; Park, Chae Haeng; Lee, Hong Kum; Cho, Jang-Cheon; Hong, Soon Gyu (Frontiers in Microbiology, 2020)
Lichens are miniature ecosystems that contain fungi, microalgae, and bacteria. It is generally accepted that symbiosis between mycobiont and photobiont and microbial contribution to the ecosystem support the wide distribution of lichens in terrestrial ecosystems, including polar areas. The composition of symbiotic components can be affected by subtle microenvironmental differences within a thallus, as well as large-scale climate differences. In this study, we investigated fine-scale profiles of algal, fungal, and bacterial compositions through horizontal and vertical positions of the Antarctic lichen Cladonia squamosa colonies by next-generation sequencing of the nuclear large subunit rRNA gene of eukaryotes and the 16S rRNA gene of bacteria. Apical parts of thalli were exposed to strong light, low moisture, and high variability of temperature compared with basal parts. Microbial diversity increased from apical parts to basal parts of thalli. Asterochloris erici was the major photobiont in apical positions of thalli, but other microalgal operational taxonomic units (OTUs) of Trebouxiophyceae and Ulvophyceae were major microalgal components in basal positions. Photochemical responses of algal components from apical and basal parts of thalli were quite different under variable temperature and humidity conditions. Several fungal OTUs that belonged to Arthoniomycetes and Lecanoromycetes, and diverse bacterial OTUs that belonged to Alphaproteobacteria, Acidobacteria_Gp1, and candidate division WPS-2 showed a clear distribution pattern according to their vertical positions within thalli. The overall lichen microbiome was significantly differentiated by the vertical position within a thallus. These results imply that different microclimate are formed at different lichen thallus parts, which can affect microbial compositions and physiological responses according to positions within the thalli.